Assessment of Extruded Root Canal Filling Materials in Single-Rooted Teeth Using Cone Beam Computed Tomography - Çulha, Emre; Tunç, Fatma (European Journal of Therapeutics, 2023)
Objective: Overfilling a root canal has a negative influence on the prognosis of teeth with apical periodontitis. This study proposed to assess extruded sealer and gutta-percha in single-rooted teeth within a Turkish subpopulation using cone-beam computed tomography. Methods: The study included cone-beam computed tomography scans of 2,346 endodontically treated teeth with a single root and foramen from a private dental clinic’s archive. Teeth were divided into four groups: maxillary anteriors, mandibular anteriors, mandibular premolars, and maxillary second premolars. Two endodontists analyzed the scans at all planes and recorded information pertaining to tooth number, tooth type, and presence of extrusion. To examine the data, a chi-square test with a 0.05 p-value was performed. Results: Extrusion was detected in 256 (10.91%) of the single-rooted teeth. There was significant difference among the groups (p<0.05). Extrusion was significantly higher in the maxillary anteriors than in the other tooth groups. Maxillary second premolars had lower extrusion compared to the other tooth groups. There was no statistical relationship between the maxillary anterior tooth groups and the presence of extrusion (p=0.338). Conclusion: Maxillary anteriors had higher root canal filling material extrusion than the other tooth groups, while maxillary second premolars had lower extrusion.